Artificial Intelligence and Service Personalization in Hospitality: Impacts on Guest Loyalty - Mufaddhal, Zaidan (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2025)
This study investigates the role of artificial intelligence in driving service personalization and its subsequent effects on guest loyalty within the hospitality industry. Drawing on service quality and technology acceptance theories, the research examines how AI service quality and AI transparency influence perceived personalization, with privacy concern as a moderating factor. A survey of 412 hotel guests who interacted with AI-enabled services was analyzed using partial least squares structural equation modeling (PLS-SEM). The findings reveal that both AI service quality and AI transparency significantly enhance perceived personalization, which in turn strongly predicts guest loyalty intentions. Mediation analysis confirms that perceived personalization serves as the key mechanism linking AI attributes to loyalty outcomes. Moreover, moderation tests indicate that privacy concern weakens the positive effects of AI service quality and transparency on personalization, underscoring the boundary conditions of AI adoption in hospitality. The study contributes to hospitality and tourism literature by providing empirical evidence that AI-driven personalization is a double-edged innovation, capable of strengthening loyalty while constrained by privacy concerns. Practical implications highlight the importance of investing in transparent, high-quality AI systems and balancing personalization with ethical data practices to foster long-term guest relationships.